PERSPECTIVAS SOBRE ATIVIDADES ANTIMICROBIANAS DE COMPOSTOS DERIVADOS 1,2,4-OXADIAZÓLICOS - Lopes, Paulo Guilherme Markus; Spader, Tatiana; Alves, Sydney Hartz; Dornelles, Luciano (Saúde (Santa Maria), 2005)
Carta ao editor.